2018
DOI: 10.15517/ma.v29i2.29546
|View full text |Cite
|
Sign up to set email alerts
|

Degradabilidad ruminal de la materia orgánica de variedades de Cenchrus purpureus tolerantes a sequía

Abstract: The main limitation of tropical grasses is their high content of structural carbohydrates, which determine the use of grass by animals. When pastures or forages grow in adverse ecosystems there are important changes in the ruminal degradability of the compounds of interest. The objective was to characterize, at different ages of regrowth, the in situ ruminal degradability of the organic matter of different varieties of Cenchrus purpureus genetically improved to tolerate dry environments. Three drought tolerant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
0
0
4
Order By: Relevance
“…Age impacts the nutritional quality of forages, producing changes in the chemical composition, which affect animal production. The ruminal degradability of grasses is related to the cell wall percentages, because the degradability of the rumen decreases as the fiber content increases (Ledea et al, 2018). Ku-Vera et al (2014) reported that tropical forages had a low CP content and a high NDF percentage, as well as a low digestibility and a lower metabolizable energy content.…”
Section: Introductionmentioning
confidence: 99%
“…Age impacts the nutritional quality of forages, producing changes in the chemical composition, which affect animal production. The ruminal degradability of grasses is related to the cell wall percentages, because the degradability of the rumen decreases as the fiber content increases (Ledea et al, 2018). Ku-Vera et al (2014) reported that tropical forages had a low CP content and a high NDF percentage, as well as a low digestibility and a lower metabolizable energy content.…”
Section: Introductionmentioning
confidence: 99%
“…El objetivo final del establecimiento de pasturas es mejorar el sistema de producción animal. Sin embargo, su ingreso a este implica considerable esfuerzo financiero en su implantación, realizando gastos de laboreo del suelo, fertilización y compra de semillas, entre otros aspectos (Ledea et al, 2018).…”
Section: Introductionunclassified
“…Esto ocasiona disponibilidad reducida de alimento para el ganado vacuno, lo que limita la producción de leche y carne (Fernández et al, 2004). Además, la calidad nutricional también cambia rápidamente, ya que con la edad experimentan modificaciones sensibles y graduales en su composición química, lo que afecta de forma general la producción animal (Ramírez et al, 2012;Ledea et al, 2018).…”
Section: Introductionunclassified
See 2 more Smart Citations